2020
DOI: 10.3960/jslrt.19039
|View full text |Cite
|
Sign up to set email alerts
|

The clinical impact of absolute lymphocyte count in peripheral blood among patients with methotrexate - associated lymphoproliferative disorders

Abstract: Regressive lymphoproliferative disorders (R-LPD) after methotrexate (MTX) withdrawal are one of the specific features of methotrexate-associated lymphoproliferative disorders (MTX-LPD). Although the impact of the absolute lymphocyte count (ALC) on the pathogenesis of R-LPD has been recently emphasized, understanding relapse/regrowth events (RRE) and differences among LPD subtypes is necessary. In this study, we confirmed ALC recovery in the regressive group

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…We demonstrated that EBV-negative status and high levels of serum LDH were both factors leading to a poor prognosis. These findings are consistent with previous studies that reported that EBV-positivity, 20,23 high levels of serum IL-2R, 30 absolute lymphocyte count, [30][31][32] and International Prognostic Index (IPI) risk 20 are all important factors associated with the likelihood of spontaneous regression in patients diagnosed with MTX-LPD.…”
Section: Discussionsupporting
confidence: 93%
“…We demonstrated that EBV-negative status and high levels of serum LDH were both factors leading to a poor prognosis. These findings are consistent with previous studies that reported that EBV-positivity, 20,23 high levels of serum IL-2R, 30 absolute lymphocyte count, [30][31][32] and International Prognostic Index (IPI) risk 20 are all important factors associated with the likelihood of spontaneous regression in patients diagnosed with MTX-LPD.…”
Section: Discussionsupporting
confidence: 93%
“…In Tokuhira et al, the absolute lymphocyte count in the peripheral blood of MTX‐LPD patients recovered rapidly in the spontaneous remission group, but did not change in the exacerbation group. 28 These recovered lymphocytes were mainly composed of Th1, effector memory B‐cells, and EBV‐specific T‐cells. 2 , 28 Based on this analysis and previous reports, we suggest that CD8‐positive T‐cells are involved in the spontaneous regression of MTX‐LPD, and PD‐1/PD‐L1 is a vital molecule for this reaction.…”
Section: Discussionmentioning
confidence: 99%
“… 28 These recovered lymphocytes were mainly composed of Th1, effector memory B‐cells, and EBV‐specific T‐cells. 2 , 28 Based on this analysis and previous reports, we suggest that CD8‐positive T‐cells are involved in the spontaneous regression of MTX‐LPD, and PD‐1/PD‐L1 is a vital molecule for this reaction. Abnormalities in the PD‐1/PD‐L1 pathway may contribute to the poor prognosis for CHL‐type MTX‐LPD caused by excessive PD‐L1 gene amplification.…”
Section: Discussionmentioning
confidence: 99%
“…In P group, there is no statistically significant difference in ALC between the time of MTX withdrawal due to MTX-LPD development and 1 month later. In other words, there seems to be no change in the ALC values (31).…”
Section: Clinical Featuresmentioning
confidence: 92%
“…Several factors associated with regression have been reported (31). Firstly, an absolute lymphocyte count (ALC) in peripheral blood is associated with regression.…”
Section: Clinical Featuresmentioning
confidence: 99%